Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1155/2014/503850
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Pumping Pressure from Concrete Composition Based on the Identified Tribological Parameters

Abstract: A new method is proposed to estimate pumping pressure based on concrete composition without experimental measurements. Previous studies show that the pumping pressure depends on the interface friction between concrete and the wall of the pumping pipes. This friction is determined by the thickness and the rheology of the boundary layer formed at the interface. The latter is mainly formed by water, cement, and fine sand particles which come from concrete. Hence, interface parameters, which are the viscous consta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 12 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…The concrete pumpability can be enhanced by increasing the cement paste volume, water-cement ratio and superplasticizer dosage (Ling and Kwan 2015;Ngo et al 2012). Although the increase of the water-cement ratio can improve pumpability, it is easy to induce segregation, bleeding and pipe blockage in the pumping process (Mai et al 2014;Felekoglu et al 2007). The pumpability is highly associated with both the workability and stability of the fresh concrete.…”
Section: Proportionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concrete pumpability can be enhanced by increasing the cement paste volume, water-cement ratio and superplasticizer dosage (Ling and Kwan 2015;Ngo et al 2012). Although the increase of the water-cement ratio can improve pumpability, it is easy to induce segregation, bleeding and pipe blockage in the pumping process (Mai et al 2014;Felekoglu et al 2007). The pumpability is highly associated with both the workability and stability of the fresh concrete.…”
Section: Proportionmentioning
confidence: 99%
“…The yield stress becomes increasingly important at lower viscosity. Different values of rheological parameters may be acquired for the same mixtures when testing by different instruments (Mai et al 2014). Kaplan et al (2005b) reported that the viscous constant (rather than the yield stress) of the lubrication layer was the major factor for pumpability.…”
Section: Rheological Parametersmentioning
confidence: 99%
“…The formation of the lubricating layer has been frequently investigated in recent years, for example by ultrasonic velocimetry [17], pressure loss measurements [15,18,19], and Particle Image Velocimetry (PIV) on the surface of the flowing material [20]. In addition, the influence on the pressure loss has been investigated by numerical simulation [21].…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [7] obtained and verified the empirical relationship between the surface strain of the pipeline and the pressure on the inner wall of the pipeline, and they also monitored the flowing concrete pressure on the inner wall of the pipeline by measuring the strain on the outer surface of the pipeline. With the help of the database which recording the interfacial yielding stress inside the pipeline, viscosity constants and concrete grading, Mai et al [8] established a computational model relating the concrete grading to yielding stress and pressure inside https://doi.org/10.1051/e3sconf/202019801001 E3S Web of Conferences , 01001 (2020) ISCEG 2020 the pipeline. This model was able to evaluate the pressure inside the pipeline with relative error around 15%.…”
Section: Introductionmentioning
confidence: 99%